2020
DOI: 10.3390/cells9061475
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transglutaminase 2 but Not of MDM2 Has a Significant Therapeutic Effect on Renal Cell Carcinoma

Abstract: More than 50% of human cancers harbor TP53 mutations and increased expression of Mouse double minute 2 homolog (MDM2), which contribute to cancer progression and drug resistance. Renal cell carcinoma (RCC) has an unusually high incidence of wild-type p53, with a mutation rate of less than 4%. MDM2 is master regulator of apoptosis in cancer cells, which is triggered through proteasomal degradation of wild-type p53. Recently, we found that p53 protein levels in RCC are regulated by autophagic degradation. Transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Animal experiments were performed as described previously [ 49 ]. Briefly, BALB/c-nu mice (female, 6–8 weeks old; Orient Bio, Seongnam, South Korea) were used to establish a tumor xenograft model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments were performed as described previously [ 49 ]. Briefly, BALB/c-nu mice (female, 6–8 weeks old; Orient Bio, Seongnam, South Korea) were used to establish a tumor xenograft model.…”
Section: Methodsmentioning
confidence: 99%
“…The immunohistochemistry of mouse xenografts was done as described previously [ 49 ] at the Laboratory Animal Research Facility (National Cancer Center). For the histological analysis, the sections were stained with hematoxylin and eosin (H&E) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have further demonstrated that p53 sequestration into autophagosomes occurs through its interaction with the enzyme TG2, which connects p53 with the autophagic protein SQSTM1/p62 [ 38 ]. Moreover, autophagy-related drug resistance appears to be mediated by TG2; therefore, the inhibition of this enzyme might prevent drug resistance, improving cancer therapy [ 66 ]. Consistently, it was reported that treatment with streptonigrin, a TG2 inhibitor, was able to reduce cancer cell growth in a xenograft model of RCC, confirming that the targeting of TG2 exerts anticancer properties [ 66 ].…”
Section: Current and New Targeted Therapies For Rcc Treatmentmentioning
confidence: 99%
“…Moreover, autophagy-related drug resistance appears to be mediated by TG2; therefore, the inhibition of this enzyme might prevent drug resistance, improving cancer therapy [ 66 ]. Consistently, it was reported that treatment with streptonigrin, a TG2 inhibitor, was able to reduce cancer cell growth in a xenograft model of RCC, confirming that the targeting of TG2 exerts anticancer properties [ 66 ].…”
Section: Current and New Targeted Therapies For Rcc Treatmentmentioning
confidence: 99%
“…IHC studies in an advanced type 1 sarcomatoid pRCC showed MDM2 expression and amplification [ 119 ]. A recent report indicated that while p53 stability in RCC was inversely related to the expression level of MDM2 and Transglutaminase 2 (TGase2, a protein involved in autophagic protein degradation), inhibition of TGase2 but not MDM2 in an in vivo RCC model had efficient anticancer effects [ 120 ]. However, MDM2 acting as an oncogenic protein may play additional roles besides controlling wild type p53.…”
Section: Mdm2 (Hdm2) In Rccmentioning
confidence: 99%